Considerações sobre alguns resultados obtidos no contexto da cosmologia newtoniana - Loiola, Danielle Lima de (2011)
The equations of motion are obtained in the framework of Newtonian cosmology using only the Newtonian dynamics and Newtonian gravity. It is shown that these equations are in close correspondence with the ones obtained in the framework of general relativity, with the scale factor satisfying the same equation in both theories, when the pressure is neglected. The characteristics of the expansion for a universe dominated by radiation, matter or vacuum are obtained. The Newtonian gravity is formulated in geometrical language. In this scenario, it is shown that for homogeneous and isotropic universes, the equation for the geodesic deviation in Newtonian cosmology is exactly the same as the geodesic equation in Einstein cosmology. We discuss possible consequences of the assumption of a Yukawa correction to the New- tonian gravitational interaction. It is shown that this correction does not introduce any modi cation in the cosmological equations. We present and discuss a result obtained concerning the growth of density perturbations in Newtonian cosmological models with creation of matter, in the case in which the pressure is neglected. Some addition comments are done for a system in which the pressure is considered. We also investigate some aspects of quantum Newtonian cosmology and construct a wave function for a universe with continuous matter creation, in the framework of non-relativistic quantum mechanics.